Development and assessment of a thermochemical cycle and SOFC-based hydrogen energy systems as a potential energy solution for the peak demand in a sustainable community - Tarique, Altaf Hasan; Khan, Sher Afghan; Khalid, Farrukh; Azami, Muhammad Hanafi (Elsevier Ltd Kidlington Corporate Office, Kidlington, United Kingdom, 2024)
In this study, an integrated energy system is presented in which hydrogen is produced via the thermochemical cycle. The presented system would provide a potential solution for storing excess electric power in terms of hydrogen generation for a sustainable community. Principles of exergy and energy are utilized to analyze the presented system in terms of exergy and energy efficiencies. The simulation result shows that with the help of the developed system, 0.36 kg/h of hydrogen can be generated, which is utilized via SOFCs to produce and electrify the houses. Additionally, the developed system can supply 1000 kW of electric power with 3.6 kW of heating. With the use of the thermochemical cycle considered in the present study, one can produce hydrogen with an energy efficiency of 79.6% and an exergy efficiency of 62.9%. Furthermore, to see the impact of different factors on the operation of the developed system, a parametric study is also conducted by changing factors like solar irradiation, the inlet temperature of the molten salt, and the outlet temperature of the solar collector.